Participatory Design with People with Disability in Rural Cambodia: The Creativity Challenge. (3rd September 2018) - Drain, Andrew; Shekar, Aruna; Grigg, Nigel
Abstract: The majority of Cambodians live rurally, with most engaged in farming practices. For people with disabilities in rural Cambodia, such as the estimated 40, 000 land mine amputees, inclusion in these practices is currently impossible. It is therefore important to strive towards the design of effective assistive technologies, as well as social empowerment, to allow these individuals better access to Cambodia's traditional livelihood. This study investigates the use of participatory design, a collaborative design process, for the identification of challenges and design of solutions with a rural community of people with disability. It discusses the implementation of creative capacity building workshops, developed in Uganda, as a tool for improving the effectiveness of designer-community collaboration. Themes such as creativity, contextual insights and inclusion were identified as challenging areas for future development while themes such as convergent thinking, prototyping and motivation were identified as strengths of the collaboration.